2020
DOI: 10.1002/oby.23018
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Physical Activity and Diet Quality with Body Composition and Fat Distribution in US Adults

Abstract: This study aimed to investigate the relationships among physical activity (PA), diet quality, body composition, and fat distribution in a representative sample of US adults. Methods: A cross-sectional analysis was conducted using publicly accessible data from the 2011 to 2016 National Health and Nutrition Examination Survey and the Food Patterns Equivalents Database (n = 7,423). Variables from the data sets were analyzed for this study, including PA, two 24-hour dietary recalls, and dual-energy x-ray absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, their results could be influenced by a range of different factors such as changes in lifestyle trends, cultural movements, economic trends, and federal policy changes. For example, one of our previous studies found that improving dietary quality improved fat distribution when accounting for other factors like sex, race/ethnicity, education and family income [28]. Given national trends in adiposity [23], it should not be surprising that there are initial increases in visceral adipose measures across most groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, their results could be influenced by a range of different factors such as changes in lifestyle trends, cultural movements, economic trends, and federal policy changes. For example, one of our previous studies found that improving dietary quality improved fat distribution when accounting for other factors like sex, race/ethnicity, education and family income [28]. Given national trends in adiposity [23], it should not be surprising that there are initial increases in visceral adipose measures across most groups.…”
Section: Discussionmentioning
confidence: 97%
“…( 4) Additionally, ratio of family income to poverty (0-4.99, 5 or above) has been classified into two categories: at or above (≥1), below poverty level (<1) [24,26]. In addition to demographics, body fat percentage has been included as one of confounding variables for certain analyses due to its possible influence on study variables [27,28].…”
Section: Confounding Variablesmentioning
confidence: 99%
“…Other factors such as the reported physical activity were low in this population and they did not differ between groups or over time; therefore, they do not explain the attenuated LBM loss in the HP group. In individuals who are not losing weight, diet quality is associated with higher LBM, with or without physical activity (34). Understanding how to preserve LBM during CR continues to be a concern in the field, and future studies might explore further whether protein sources in combination with other foods affect LBM.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect body composition, and diet and level of physical activity are some of the most important aspects to be considered (4,5). Low-carbohydrate diets, for example, may be effective in decreasing FM in obese individuals (6), whereas high-protein diets may have a beneficial effect on weight loss, increasing FM loss and preserving fat-free mass (FFM) (7).…”
Section: Introductionmentioning
confidence: 99%